Models for microtubule cargo transport coupling the Langevin equation to stochastic stepping motor dynamics: Caring about fluctuations - Bouzat, Sebastian (American Physical Society, 2016)
Fil: Bouzat, Sebastián. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina